2020
DOI: 10.31234/osf.io/pmwu2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Struggles and Strategies in Anaerobic and Aerobic Cycling Tests: A Mixed-Method Approach With a Focus on Tailored Self-Regulation Strategies

Abstract: Endurance sports pose a plethora of psychological demands that athletes have to deal with. Unfortunately, fine-grained investigations of these demands and strategies for coping with them are lacking, severely limiting our knowledge about endurance performance. Here, we investigated the obstacles exercisers experienced during an anaerobic (Wingate test) and an aerobic cycling test (incremental exercise test), as well as the strategies they considered helpful for dealing with these obstacles. In addition, we tes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Besides being inherently linked to effort, engaging in sports and exercise can also be plain boring (as exemplified by the quote from Veiko Karvonen above). For instance, boredom has recently been identified as a frequent obstacle during aerobic endurance exercises ( Hirsch et al, 2020 ). On the other hand, sports and exercise can also be used to alleviate boredom ( Morris et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being inherently linked to effort, engaging in sports and exercise can also be plain boring (as exemplified by the quote from Veiko Karvonen above). For instance, boredom has recently been identified as a frequent obstacle during aerobic endurance exercises ( Hirsch et al, 2020 ). On the other hand, sports and exercise can also be used to alleviate boredom ( Morris et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being inherently linked to effort, engaging in sports and exercise can also be plain boring (as exemplified by the quote from Veiko Karvonen above). For instance, boredom has recently been identified as a frequent obstacle during aerobic endurance exercises 20 . On the other hand, sports and exercise can also be used to alleviate boredom 21 .…”
Section: Exercise Can Be Boringmentioning
confidence: 99%
“…Researchers therefore identified boredom as an experience that may play an important role in most leisure activities (Bösselman et al, 2021;Deck et al, 2020;McCurdy et al, 2022). For instance, Hirsch et al (2021) found that boredom was a common barrier for aerobic endurance training, whereas Morris et al (2003) suggested that sport and physical activity can reduce boredom. This proves that boredom has a multi-faceted role to play in the context of leisure physical activity.…”
Section: Introductionmentioning
confidence: 99%